The Role Of Translation Criticism In Enhancing Translation Quality And Fostering Translator Creativity: A Critique Of The Arabic Translation Of Lord Of The Flies By William Golding As A Case Study.: دور نقد التّرجمة في تحسين جودة التّرجمة وتعزيز إبداع المترجم: نقد التّرجمة العربيّة لرواية أمير الذباب لويليام غولدنغ كدراسة حالة - KADRI, Abdeldjalil; MAZOUZ, Soumaya (Maalim, 2025)
This paper examines how translation criticism can enhance the quality of literary translations and the creativity of translators while preserving the cultural and symbolic integrity of the original text. Through William Golding’s Lord of the Flies, the study highlights how translation criticism can maintain the richness, depth, and symbolism of the original text while adapting it for new audiences. The study explores how theoretical frameworks like hermeneutics and semiotics can guide critics in assessing translations, ensuring that the translator’s choices align with the author’s intentions and cultural context. Ultimately, the article argues that translation criticism is an essential tool for refining translations, promoting cross-cultural understanding, and enriching literary experiences.